Borophene as an extremely high capacity electrode material for Li-ion and Na-ion batteries. Issue 33 (9th August 2016) - Zhang, Xiaoming; Hu, Junping; Cheng, Yingchun; Yang, Hui Ying; Yao, Yugui; Yang, Shengyuan A.
Abstract : The Li/Na storage capacities in borophene are the highest among all the 2D electrode materials discovered to date. Abstract : "Two-dimensional (2D) materials as electrodes" is believed to be the trend for future Li-ion and Na-ion battery technologies. Here, by using first-principles methods, we predict that the recently reported borophene (2D boron sheets) can serve as an ideal electrode material with high electrochemical performance for both Li-ion and Na-ion batteries. The calculations are performed on two experimentally stable borophene structures, namely β12 and χ3 structures. The optimized Li and Na adsorption sites are identified, and the host materials are found to maintain good electric conductivity before and after adsorption. Besides advantages including small diffusion barriers and low average open-circuit voltages, most remarkably, the storage capacity can be as high as 1984 mA h g −1 in β12 borophene and 1240 mA h g −1 in χ3 borophene for both Li and Na, which are several times higher than the commercial graphite electrode and are the highest among all the 2D materials discovered to date. Our results highly support that borophenes can be appealing anode materials for both Li-ion and Na-ion batteries with extremely high power density.